Digital Work in the Planetary Market - Mark Graham; Fabian Ferrari (The MIT Press, 2022)
Understanding the embedded and disembedded, material and immaterial, territorialized and deterritorialized natures of digital work. Many jobs today can be done from anywhere. Digital technology and widespread internet connectivity allow almost anyone, anywhere, to connect to anyone else to communicate and exchange files, data, video, and audio. In other words, work can be deterritorialized at a planetary scale. This book examines the implications for both work and workers when work is commodified and traded beyond local labor markets. Going beyond the usual "world is flat" globalization discourse, contributors look at both the transformation of work itself and the wider systems, networks, and processes that enable digital work in a planetary market, offering both empirical and theoretical perspectives. The contributors—leading scholars and experts from a range of disciplines—touch on a variety of issues, including content moderation, autonomous vehicles, and voice assistants. They first look at the new experience of work, finding that, despite its planetary connections, labor remains geographically sticky and embedded in distinct contexts. They go on to consider how planetary networks of work can be mapped and problematized, discuss the productive multiplicity and interdisciplinarity of thinking about digital work and its networks, and, finally, imagine how planetary work could be regulated. Contributors Sana Ahmad, Payal Arora, Janine Berg, Antonio A. Casilli, Julie Chen, Christina Colclough, Fabian Ferrari, Mark Graham, Andreas Hackl, Matthew Hockenberry, Hannah Johnston, Martin Krzywdzinski, Johan Lindquist, Joana Moll, Brett Neilson, Usha Raman, Jara Rocha, Jathan Sadowski, Florian A. Schmidt, Cheryll Ruth Soriano, Nick Srnicek, James Steinhoff, Jara Rocha, JS Tan, Paola Tubaro, Moira Weigel, Lin Zhang
Keywords: 330; Labour / income economics; E-commerce: business aspects; Central / national / federal government policies